Multiple Sclerosis: The Hidden Symptoms - Ansh Chaudhary; Bhupendra Chaudhary (Issues and Developments in Medicine and Medical Research Vol. 9, 2022)
Multiple sclerosis (MS), with its diverse central and peripheral nervous system symptoms, poses a challenge to its care in a variety of clinical scenarios. The issue becomes much more complicated with occurrence of strange and unusual symptoms intermingling with common symptoms in people living with MS. The frequency and severity of these unusual symptoms changes overtime and raise a suspicion of other neurological disease. The occurrence of any of these symptoms at times may be a sign of active disease. A reasonable understanding of these strange symptoms both to the patient and healthcare team could be of help in taking appropriate steps to manage MS more efficiently. Unusual and rare manifestation can be a part of the MS constellation of symptoms, so it is important to identify as these invisible or uncommon symptoms are experienced differently by these MS patients so tracking these symptoms is another way to manage MS more efficiently